The most efficient level of winter protein feeding for yearling steers wintered and summer grazed on bluestem pasture. - Smith, E.F.; Baker, F.H.; Cox, R.F.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
Twenty head of good-quality Hereford yearling steers, 10 per lot. were used. They were purchased as steer calves in the fall of 1953 from the Brite Ranch at Marfa, Texas, and used in summer grazing tests on bluestem pasture in 1953. During the winter phase of this test the steers were moved from pasture to pasture every 16 days to minimize any differences due to pastures. The winter pastures the steers were grazed in had been stocked at normal rate during summer, but had sufficient grass remaining to provide ample winter grazing. In addition to dry bluestem pasture, the steers were fed in the following manner during the winter: Lot 1-1 pound of cottonseed cake per head daily. Lot 2-2 pounds of cottonseed cake per head daily. The steers of both lots were grazed together during the summer of 1954.
Keywords: Beef; Protein; Bluestem pasture; Yearling steers